X-chromosome-wide association study for Alzheimer’s disease - Le Borgne, Julie; Gomez, Lissette; Heikkinen, Sami; Amin, Najaf; Ahmad, Shahzad; Choi, Seung Hoan; Bis, Joshua C.; Grenier-Boley, Benjamin; Rodriguez, Omar Garcia; Kleineidam, Luca; Young, Juan; Tripathi, Kumar Parijat; et al. (Molecular psychiatry, 2025)
Due to methodological reasons, the X-chromosome has not been featured in the major genome-wide association studies on Alzheimer’s Disease (AD). To address this and better characterize the genetic landscape of AD, we performed an in-depth X-Chromosome-Wide Association Study (XWAS) in 115,841 AD cases or AD proxy cases, including 52,214 clinically-diagnosed AD cases, and 613,671 controls. We considered three approaches to account for the different X-chromosome inactivation (XCI) states in females, i.e. random XCI, skewed XCI, and escape XCI. We did not detect any genome-wide significant signals (P ≤ 5 × 10−8) but identified seven X-chromosome-wide significant loci (P ≤ 1.6 × 10−6). The index variants were common for the Xp22.32, FRMPD4, DMD and Xq25 loci, and rare for the WNK3, PJA1, and DACH2 loci. Overall, this well-powered XWAS found no genetic risk factors for AD on the non-pseudoautosomal region of the X-chromosome, but it identified suggestive signals warranting further investigations.